1985
DOI: 10.1099/00221287-131-3-527
|View full text |Cite
|
Sign up to set email alerts
|

The all2 Gene is Required for the Induction of the Purine Deamination Pathway in Schizosaccharomyces pombe

Abstract: Five mutants were isolated at the all2 gene on the basis of their inability to utilize hypoxanthine as a sole source of nitrogen. These mutants failed to utilize the purines adenine, hypoxanthine, xanthine, uric acid, allantoin and allantoic acid, although they could utilize urea and ammonium. The all2 mutants appeared to be defective in purine induction of uricase, allantoinase, allantoicase and ureidoglycollase activities but retained wild-type activity of the constitutively synthesized urease. The all2 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Bacterial alanine racemases belong to fold type III (7,9,11), while fungal alanine racemase belongs to fold type I (4,12). This is probably a case of convergent evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial alanine racemases belong to fold type III (7,9,11), while fungal alanine racemase belongs to fold type I (4,12). This is probably a case of convergent evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Fluri and Kinghorn [107] suggested that a single gene ( all2 ) is involved in uricase induction and activity in Schizosaccharomyces pombe . Five mutants were isolated at the a112 gene on the basis of their inefficacy to utilize hypoxanthine as a sole source of nitrogen.…”
Section: Genetics and Uricase Encoding Genesmentioning
confidence: 99%
“…It is known, for example, that Pseudomonas aeruginosa possesses allantoinase activity (15), and a strain with a defective allantoinase gene, named puuE (purine utilization E), has been described (16). Similarly, allantoinase activity and a mutant strain that cannot grow on media containing allantoin as a sole nitrogen source have been identified in Schizosaccharomyces pombe (17). Yet genes coding for allantoinase do not appear to be present in the genomes of these organisms.…”
mentioning
confidence: 99%